2000
DOI: 10.1074/jbc.m003171200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coatomer and Phospholipids in GTPase-activating Protein-dependent Hydrolysis of GTP by ADP-ribosylation Factor-1

Abstract: The binding of the coat protein complex, coatomer, to the Golgi is mediated by the small GTPase ADP-ribosylation factor-1 (ARF1), whereas the dissociation of coatomer, requires GTP hydrolysis on ARF1, which depends on a GTPase-activating protein (GAP). Recent studies demonstrate that when GAP activity is assayed in a membrane-free environment by employing an amino-terminal truncation mutant of ARF1 (⌬17-ARF1) and a catalytic fragment of the ARF GTPase-activating protein GAP1, GTP hydrolysis is strongly stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
63
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 44 publications
9
63
0
Order By: Relevance
“…This model is consistent with a result that Pap␤ exhibits efficient catalytic GAP activity for GTP-Arf1 in vitro (18). It should also be noted that there are several reports contradictory to Goldberg's model, suggesting that the coatomer may simply aid the productive association of Arf1 and ArfGAP1 (17,19,20). On the other hand, a study on the interface array of protein interactions of the small GTPases indicates that the protein-protein contacts in the Arf1-ArfGAP1 complex are significantly different from those found in other GAP and small GTPase complexes (21).…”
supporting
confidence: 76%
“…This model is consistent with a result that Pap␤ exhibits efficient catalytic GAP activity for GTP-Arf1 in vitro (18). It should also be noted that there are several reports contradictory to Goldberg's model, suggesting that the coatomer may simply aid the productive association of Arf1 and ArfGAP1 (17,19,20). On the other hand, a study on the interface array of protein interactions of the small GTPases indicates that the protein-protein contacts in the Arf1-ArfGAP1 complex are significantly different from those found in other GAP and small GTPase complexes (21).…”
supporting
confidence: 76%
“…Goldberg's model is based on the finding that the addition of coatomer to Arf1p and ArfGAP enhances GTP hydrolysis on Arf1p several orders of magnitude and it is suggested that coatomer may contribute an arginine finger residue. However, this model has been challenged by the finding that under certain conditions lipid can also accelerate the rate of GTP hydrolysis and that the addition of coatomer does not further increase this rate (Szafer et al, 2000). Also, the binding site for ArfGAP on Arf1p seems to be incompatible with the crystal structure of another ArfGAP, PAP␤.…”
Section: Mutations In Proposed Arfgap-binding Site Of Arf1pmentioning
confidence: 95%
“…Alternatively, they may indicate that residues implicated by crystallographic studies to interact with ArfGAP are not critical for the mechanism of GTP hydrolysis. Indeed, the precise mechanism by which ArfGAP catalyzes GTP hydrolysis on Arf proteins remains controversial (Goldberg, 1999;Mandiyan et al, 1999;Szafer et al, 2000). The structure of Arf1p complexed with ArfGAP was solved for the GDPbound form of Arf1p, the product of the reaction, so no direct information about the role of particular residues in the mechanism of GTP hydrolysis is available.…”
Section: Mutations In Proposed Arfgap-binding Site Of Arf1pmentioning
confidence: 99%
“…Proteins were expressed in the BL21/DE3 Escherichia coli strain harboring pLysS by induction for 3 h at 30°C in the presence of 0.1 mM isopropyl-␤-D-thiogalactopyranoside. Bacterial pellets were extracted with 6 M guanidine hydrochloride, and proteins were purified to near homogeneity by nickel-nitrilotriacetic acid chromatography followed by dialysis and Resource Q chromatography as previously described (27).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas the catalytic domain of ArfGAP1 contains the machinery required for the catalysis of GTP hydrolysis (17,27), the non-catalytic part contains information for the targeting of ArfGAP1 to the Golgi, as indicated by the correct targeting of GFP fusions of non-catalytic fragments (28). The non-catalytic part mediates the interaction of ArfGAP1 with loosely packed lipids (24) and is also involved in protein-protein interactions, as demonstrated for the interaction of ArfGAP1 with the COPI cargo, the KDEL receptor (29,30).…”
mentioning
confidence: 99%